2020
DOI: 10.1002/acn3.51012
|View full text |Cite
|
Sign up to set email alerts
|

MIDN locus structural variants and Parkinson's Disease risk

Abstract: Dear Editor, Based on a candidate gene analysis, Obara and colleagues previously reported an association between Parkinson's disease (PD) and deletion structural variants (SV)s at the MIDN locus in the Japanese population. 1 In their recent study, using genotyping data from a British cohort, Obara and colleagues further suggest MIDN as a confirmed and universal risk factor of PD. 2 To establish the pathogenicity of MIDN, as part of the International Parkinson's Disease Genomics Consortium (IPDGC), we utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
7
1
Order By: Relevance
“…However, Billingsley et al showed that no PDassociated deletions within the MIDN locus were identified by whole genome sequencing and no common deletions were detected in general populations. 11) We assume that discrepancies between our conclusions and those of Billingsley et al reflect the different methodologies used in the studies. 12) We identified no MIDN loss in healthy controls in the Yamagata cohort study, possibly because of Japanese genetic characteristics or because our previous Yamagata cohort study was not large enough to identify MIDN structural variants unlike in the large British population.…”
Section: Introductioncontrasting
confidence: 68%
“…However, Billingsley et al showed that no PDassociated deletions within the MIDN locus were identified by whole genome sequencing and no common deletions were detected in general populations. 11) We assume that discrepancies between our conclusions and those of Billingsley et al reflect the different methodologies used in the studies. 12) We identified no MIDN loss in healthy controls in the Yamagata cohort study, possibly because of Japanese genetic characteristics or because our previous Yamagata cohort study was not large enough to identify MIDN structural variants unlike in the large British population.…”
Section: Introductioncontrasting
confidence: 68%
“…Although typical DNA-binding or transcription-activating domains have not been identified in the MIDN protein, MIDN affects the transcription levels of a number of genes, including PD-related genes (Obara and Ishii, 2018), indicating that MIDN functions as a transcription modulator. Thus, we believe that MIDN loss is associated with PD although this is controversial (Billingsley et al, 2020;Obara et al, 2020).…”
Section: )mentioning
confidence: 95%
“…Diff olp is the overlapping part of two segments' alignment on the reference and it can not be too large if there exists a real large INS or large DEL. VolcanoSV decides a large INS exits if the following conditions apply Dif f olp < 3000bp Dif f dis ≥ 30bp (6) or a large DEL exits if the following conditions apply…”
Section: Volcanosv Workflowmentioning
confidence: 99%